The ethical-legal evolution of medical liability - Parra Sepúlveda, Darío Andrés (Acta Bioethica, 2014)
This paper has as goal to describe briefly the evolution of medical liability throughout history, development which allows to verify that physician activity has not only been regulated by deontological principles, but, since ancient times, there has been an interest by legislators to establish behavior parameters in this matter. Such incipient regulation was not adopted by our norms, in spite of being present in some of the sources that Bello counted when writing the Civil Code; rather, a general clause of responsibility was preferred by our legislator; this gives rise to a long period —which ends in our understanding with the promulgation of law 20.584— in which, together with the Hippocratic oath, the deontological code for physicians was the only normative body which established clearly a catalog of rights and obligations for the professional.